2461. Safety of Quadrivalent Meningococcal Polysaccharide Diphtheria Toxoid-Conjugate Vaccine in Adolescents. (26th November 2018) - Myers, Tanya; Weintraub, Eric; McNeil, Michael; Sukumaran, Lakshmi; Duffy, Jonathan; Baxter, Roger; Klein, Nicola P; Daley, Matthew F; Donahue, James; Tseng, Hung Fu; Irving, Stephanie; Jackson, Michael L; et al.
Abstract: Background: The first quadrivalent meningococcal conjugate vaccine (MenACWY-D) was recommended for use in adolescents in 2005. Soon after, case reports of Guillain-Barre syndrome (GBS) following vaccination prompted subsequent studies, with a meta-analysis concluding that the attributable risk of GBS after MenACWY-D is unlikely to exceed 1 case per million vaccinations. We conducted a retrospective cohort study in the Vaccine Safety Datalink to assess the risk of 10 outcomes, including GBS, following MenACWY-D. Methods: We included adolescents (aged 11–18 years) vaccinated with MenACWY-D during the years 2005–2014. We identified pre-specified outcomes using ICD-9 (International Classification of Disease, version 9) codes. We used automated data only for Bell's palsy, fever, seizure and syncope, and we confirmed incident cases by medical record review for acute disseminated encephalomyelitis (ADEM), acute transverse myelitis (ATM), anaphylaxis, chronic inflammatory demyelinating polyneuropathy (CIDP), GBS and Henoch-Schönlein purpura (HSP). We used a self-controlled risk interval design to estimate relative risk (RR). Results: Following 1.4 million doses of MenACWY-D, we detected increased risks for fever in the 1–6 days following vaccination (RR 1.5, 95% confidence interval [CI] 1.3–1.7) and syncope on the day of vaccination (RR 5.8, 95% CI 4.1–8.3), but not for seizures (RR 1.1, 95% CI 0.7–1.9) or Bell's palsy (RR 1.1, 95% CI 0.8–1.5). We detected no cases in the post-vaccination risk intervals for CIDP, ADEM or ATM. We detected few cases of the other outcomes resulting in relatively unstable RR estimates: anaphylaxis (RR 1.9, 95% CI 0.5–7.1), GBS (RR 2.5, 95% CI 0.6–10.0) and HSP (RR 1.6, 95% CI 0.7–3.3). We estimated that the attributable risk of GBS was 1.5 cases per million vaccinations (upper bound of one-sided 95% CI, 4.9). Conclusion: In a large retrospective cohort, we detected increased risks for syncope and fever, but not seizures or Bell's palsy, following vaccination with MenACWY-D. Other outcomes were rare. Our findings, consistent with previous studies, suggest that the increased risk of GBS, if any, is likely small (<5 excess cases of GBS per million vaccinations). Disclosures: N. P. Klein, Sanofi Pasteur: Investigator, Research grant. Merck: Investigator, Research grant. GSK: Investigator, Research grant. Pfizer: Investigator, Research support. Protein Science: Investigator, Research grant. MedImmune: Investigator, Research grant. Dynavax: Research Contractor, Grant recipient. M. L. Jackson, Novartis: Grant Investigator, Research support.